The role of the Middle East in foreign textbooks: an examination of the Egyptian market - Awaad, Amira (AUC Knowledge Fountain, 2013)
The purpose of this study is to evaluate the educational textbook market in Egypt as well as analyze the potential impact of newer textbooks published by major textbook publishers that include elements of Egyptian/Arab heritage; history, art and literature. A market analysis was conducted by examining the responses of stakeholders from an American private school in Cairo, Egypt. The educational construct, here, is a formal American, private K-12 school in Egypt.The feasibility study will be conducted to assist the publishers in making the decision that will be in the best interest of the textbook selection procedure. From this school the following participants were examined in the study: three focus groups of parents/guardians, each containing five members, three focus groups of students from the twelfth grade, each containing five members, and three focus groups of teachers, each containing five members.Based on this study, textbook publishers will understand that post 25th January, 2011, a window of opportunity has opened in Egypt with a growing demand for their services.